2020
DOI: 10.2478/hukin-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Velocity Strength Training on Movement Velocity and Strength Endurance in Experienced Powerlifters with Cerebral Palsy

Abstract: The present study aimed to evaluate the effects of a 6-week high-velocity strength training (HVST) intervention on movement velocity and strength endurance in experienced powerlifters with cerebral palsy (CP). Eleven experienced powerlifters with CP and seven from a control group (CON), were subjected to 6-week HVST. An assessment of movement velocity and strength endurance was conducted one week before (T1) and one week after (T2) the 6-week training intervention. During testing, athletes performed a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 47 , 48 , 49 , 50 ] explored the impact of the disability and the type of disability in PP. Gołaś et al [ 47 ] compared two elite flat BP athletes—an elite able-bodied athlete (aged 34 years, body weight 103 kg) and an athlete with a lower limb disability (aged 31 years, body weight 92 kg)—in terms of the activity of four muscles ( pectoralis major , anterior deltoid, lateral and long heads of the triceps brachii ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is significant information that can be derived from the current data. Powerlifting is a sport discipline in which lifters often take part in research related to strength performance [ 8 , 9 , 15 ], therefore, it should be clearly determined whether and what effect the supportive gear has on the maximum loads lifted during particular powerlifting disciplines. The margin of differences between maximal loads lifted in the EQ compared to the RAW division is related to the powerlifting discipline.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies focused on PP have addressed issues of heating, biomechanical procedures, as well as the use of supplements, or even the aetiology of injuries [3,[13][14][15][16][17][18][19][20]. However, recovery is a crucial point in sports training [21] and involves load control leading to functional adaptations, preventing and managing stress [22,23].…”
Section: Introductionmentioning
confidence: 99%